PREVALENCE AND INDICATION AND OUTCOME OF CESAREAN SECTION IN JUGAL HOSPITAL, HARARI REGIONAL STATE, ETHIOPIA, 2019: A RETROSPECTIVE STUDY - Jamie, Arif Hussen (Public Health of Indonesia, 2019)
Background: Rising rates of cesarean delivery is becoming a concern to developing countries. Though cesarean section is a lifesaving surgical intervention, the rise in rates has resulted in significant health problems of mothers and newborns. Objective: The aim to undertaking this research is to know the prevalence, indications and outcome of cesarean section delivery In Jugal Hospital, Harari regional state, Ethiopia.Methods: Hospital based record review cross-sectional study was conducted in Jugal Hospital, Harar, Ethiopia from September 1, 2015 to September 1, 2019. Trained data collector and the principal investigator collected data employing a pre-tested extraction format. After checking the filled extraction format for completeness, data was entered, cleaned and analyzed using SPSS software Version 20.Results: In five years' time (2015-2019), there were 6,111 deliveries, of which 1,817 were delivered by cesarean section which gives the overall rate of 29.7%. The most common indications for cesarean section were Cephalo-pelvic Disproportion (CPD) 323 (17.78%) followed by fetal distress 292(16.07%) and the least indication was pre-eclampsia 9(0.5%) and the most cause of prenatal death was birth asphyxia 38% followed by prematurity34%.Conclusion: In this study, there is a steady increase in the rates of cesarean delivery in five years' time, the overall rate of C-section in Jugal Hospital was 29.7%. This rate is higher than the World Health Organization standard. Policies and efforts aimed at decreasing the unnecessary cesarean sections should be promoted and implemented at each health facility.